Membangun Lemma Ekonomi Islam Berbasis Qawâ’id al-Fiqhiyah (Studi Kasus الضرر يزال) - Sugianto Sugianto (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2014)
Lemma is a statement that can be accepted as a theoretical assumptions derived from axioms. A theory is formed as a reflection of reality and proportion of the lemma is sourced from the axiom that the level of its truth comes from revelation. This paper aims to explore qawâ'id al-fiqhiyah, including al-dhararu yuzâl, as a statement from the ultimate source of truth, revelation (al-Quran and Hadith) as a lemma to build Axioma in economic studies. This axiom then is made as basic arguments in the compilation of Islamic economic theory.